2009
DOI: 10.1094/mpmi-22-7-0809
|View full text |Cite
|
Sign up to set email alerts
|

The Putative Secreted Serine Protease Chp-7 Is Required for Full Virulence and Induction of a Nonhost Hypersensitive Response by Clavibacter michiganensis subsp. sepedonicus

Abstract: Molecular biological studies on Clavibacter michiganensis subsp. sepedonicus, the causal agent of bacterial ring rot of potato, have gained greater feasibility due to the recent availability of whole genomic sequences and genetic tools for related taxa. Here, we describe the first report of construction and characterization of a transposon (Tn) mutant library of C. michiganensis subsp. sepedonicus sp. strain R10. Since virulence of R10 in potato has been shown previously to be associated with elicitation of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 31 publications
(57 reference statements)
0
35
0
Order By: Relevance
“…The chp-7 S232T derivative was made by PCR using KOD Hot Start DNA polymerase (Novagen, CA) using pRLSTC7 (Syverson 2011) as template with primers C7_S232T_F and C7_S232T_R followed by self-ligation with T4 DNA ligase (New England Biolabs, MA), resulting in pRLSTC7ST. Both plasmids were transformed into competent cells of CmsC7X20 by electroporation at 1.5 kV in cuvettes with a 1 mm gap width as previously described (Nissinen et al 2009). C-terminal FLAG epitope tags were inserted into pHNC7 and pHNC7ST by PCR with primers C7_OLpHN_F, C7_FLAG_R and FLAG_OLpHN_R, followed by ligation using the Gibson assembly cloning kit (New England Biolabs, MA) into pHN216 cut open with EcoRI, resulting in pHNC7-F and pHNC7ST-F.…”
Section: Cloning and Site-specific Mutagenesis Of Chp-7mentioning
confidence: 99%
See 2 more Smart Citations
“…The chp-7 S232T derivative was made by PCR using KOD Hot Start DNA polymerase (Novagen, CA) using pRLSTC7 (Syverson 2011) as template with primers C7_S232T_F and C7_S232T_R followed by self-ligation with T4 DNA ligase (New England Biolabs, MA), resulting in pRLSTC7ST. Both plasmids were transformed into competent cells of CmsC7X20 by electroporation at 1.5 kV in cuvettes with a 1 mm gap width as previously described (Nissinen et al 2009). C-terminal FLAG epitope tags were inserted into pHNC7 and pHNC7ST by PCR with primers C7_OLpHN_F, C7_FLAG_R and FLAG_OLpHN_R, followed by ligation using the Gibson assembly cloning kit (New England Biolabs, MA) into pHN216 cut open with EcoRI, resulting in pHNC7-F and pHNC7ST-F.…”
Section: Cloning and Site-specific Mutagenesis Of Chp-7mentioning
confidence: 99%
“…One close homolog of pat-1, named chp-7 (CMS_2989), has been identified as an important virulence factor of Cms required for full symptom development in infected potato and eggplant but not for colonization (Nissinen et al 2009). Like Pat-1, Chp-7 contains a predicted catalytic histidine at position 97 within a TAKHC motif and the predicted nucleophilic serine at position 232 within a GDSGG motif (Nissinen et al 2009). Though no proteolytic activity has been demonstrated for any of the pat-1 family serine proteases, the serine protease activity of Pat-1 is thought to be involved in virulence of Cmm in tomato, as exchanging the putative catalytic serine for threonine in Pat-1 rendered it unable to restore the virulence of the plasmid-free strain CMM100 (Burger et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a pathogenicity factor, serine protease has been reported from various pathosystems (Dow et al, 1990;Dreier et al, 1997;Nissinen et al, 2009;Redman and Rodriguez, 2002). Dow et al (1990) suggested that the role of bacterial proteases may be nutritional or, alternatively, that they could aid in the infection process through the proteolysis of structural proteins in plant cell walls.…”
Section: Pro1 As a Pathogenicity Factormentioning
confidence: 99%
“…In the potato ring rot pathogen C. michiganensis ssp. sepedonicus , a secreted serine protease Chp‐7 has been identified and proven to be required for full virulence and induction of a nonhost hypersensitive response (Nissinen et al ., 2009). Redman and Rodriguez (2002) demonstrated that an extracellular serine protease is required for the pathogenicity of Colletotrichum coccodes , and that the elimination of protease activity transforms a virulent pathogen to an avirulent endophyte.…”
Section: Introductionmentioning
confidence: 99%